Depth Analysis of Fe2O3-Incorporated Cobalt Synthesized via Gelatin-Modified Silica as Hard Template for Methylene Blue Photodegradation - Ulfa, Maria; Rohmah, Istinganah Saetu (Indonesian Journal of Chemistry, 2026)
The escalating occurrence of methylene blue (MB) contamination from textile wastewater underscores the urgent demand for effective photocatalytic remediation. This study presents a depth analysis of Fe2O3-incorporated cobalt photocatalysts synthesized using a gelatin-modified silica hard-template method, followed by calcination at 300 and 550 °C. Structural characterization via XRD, FTIR, and EDX confirmed enhanced crystallinity and Co–O phase formation at elevated temperatures, while BET analysis revealed a reduction in surface area (123.4 to 104.5 m2/g) and pore volume (0.2236 to 0.1875 cm3/g) due to sintering and template removal. FTIR data indicated the attenuation of hydroxyl and water-related bands, suggesting decreased surface hydration at higher temperatures. Despite the decline in surface metrics, α-Fe2O3–Co–550 exhibited superior photocatalytic efficiency, achieving greater than 90% MB degradation under visible light, attributed to an increased cobalt content (Fe:Co≈2:1), improved phase purity, and an optimized electronic structure. Kinetic modeling revealed pseudo-first-order behavior for both samples, with α-Fe2O3-Co-300 showing a higher rate constant (K1 = 0.01116 min−1) yet lower overall degradation performance than α-Fe2O3-Co-550, highlighting the critical interplay of structural order, charge transfer efficiency, and compositional tuning enabled by hard-template synthesis for effective photocatalytic wastewater treatment.